RELIGIOUS MODERATION: TOLERANCE VALUES IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE MUARO JAMBI TEMPLE COMPLEX - Abdul Wahid; Sayed; Anita Sari; M. Rohimin; Fia Alifah Putri (Darul Ilmi Bina Insan Foundation, 2025)
This study explores the implementation of religious moderation through tolerance values in Islamic Religious Education within the Muaro Jambi Temple Complex. Employing a descriptive qualitative approach, the study analyzes how tolerance is practiced and interpreted by the local Muslim community, traditional leaders, and educators. The data were examined to identify patterns and relationships that reflect the integration of religious principles with the social and cultural context of the site. The findings reveal that tolerance is demonstrated through the community’s ability to maintain strong religious commitment while simultaneously respecting and preserving the cultural and historical heritage. 1) The temple environment is used as a living laboratory for learning, where teachers of Annisa Kindergarten and Itihadul Khoiriyah MTs integrate wasathiyah values through a contextual, historical, and experiential learning pedagogical approach that provides opportunities for students to understand cultural diversity; practice tolerance, and avoid extreme judgments of differences. 2) The community remains steadfast in the value of monotheism while interpreting the existence of historical sites as part of a cultural identity that needs to be maintained, so that their religious practices are inclusive, balanced, and harmonious, in line with the paradigm of Islam rahmatan lil 'alamin; 3) Socio-religious life, worship activities, and educational activities take place side by side with the flow of cultural tourism without conflict, indicating a strong internalization of religious moderation at the practical level